Performance analysis of refrigeration system with 1 pk compressor based on evaporator temperature variation - M. Sugiri; Indra Widarmadi; Parman Sinaga (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
Refrigeration machines or also called cooling machines are machines that can cause the refrigeration effect, while refrigerants are substances used as working fluids in the heat absorption process. Refrigeration is a process of absorbing heat from a substance or product so that its temperature is below the ambient temperature. The purpose of the study was to analyze the performance of the refrigeration machine and the research method used was the experimental method by testing a 1 PK cooling machine using R134a refrigerant with temperature variations in the evaporator room. The results of this study showed that the performance of the refrigeration system to reach a temperature of -15º C took 7 hours 45 minutes with a load of 10 liters of water. The lowest compressor power value was 0.5307 kW and the highest was 0.6566 kW. The lowest compressor work value was 32 kJ/kg and the highest was 41 kJ/kg. The lowest heat value released by the condenser was 1.95 kW and the highest was 2.698 kW. The lowest calorific value absorbed by the evaporator is 1.43 kW and the highest is 2.09 kW, the lowest refrigerant mass flow rate value is 0.013 kg/s and the highest is 0.019 kg/s. The lowest actual COP value is 2.69 and the highest is 3.43.